EFFECTS OF EMPLOYEE MOTIVATION STRATEDIES ON EMPLOYEE PERFORMANCE IN TELECOMMUNICATION COMPANIES IN SOMALIA - Yusuf, Mohamed Abdirizak Sh; GICHINGA, LUCY (IJRDO - Journal of Business Management, 2016)
Motivation plays an important role in all public and private organizations. Without motivating their employees organizations can’t run and can’t achieve their goals. Motivation and performance of the employees are essential tools for the success of any organization in the long run. On the one hand, measuring performance is critical to organization’s management, as it highlights the evolution and achievement of the organization. On the other hand, there is a positive relationship between employee motivation and organizational effectiveness, reflected in numerous studies. This research aims to analyze the drivers of employee motivation to high levels of organizational performance. The literature shows that factors such as empowerment and recognition increase employee motivation. If the empowerment and recognition of employees is increased, their motivation to work was also improve, as well as their accomplishments and the organizational performance. Nevertheless, employee dissatisfactions caused by boring jobs and pressure from clients, might weaken the organizational performance. The Purpose of this study is to explore the effect of motivation on employee’s performance of telecommunication companies in Somalia. The study has the following objectives; to assess the extent to which financial incentives influences employee performance. To assess the extent to which training and development influences employee performance, to determine the effect of employee empowerment on employee performance. The study was utilized descriptive research design in order to describe the variables of the study. The target population of this study was 5000 and sample size of 98. The Data was being collected used structured questionnaire as a research instrument. The data was being analyzed using percentages, frequencies, graphs and regression analysis with the help of Statistical Package for Social Science (SPSS version 22). Respondents agree on financial incentives affects employee performance. The respondents agreed that the bonuses and extras added yearly to my salary make me feel satisfied. The study sought to establish the effects Training and Development on employee performance of telecommunication companies in Mogadishu Somalia From the findings respondents agreed in our organization training motivates employees to be more committed towards organizational goals and also results are consistent with the findings obtained on training has helped me in improving my overall required skills for work . The respondent also agreed I believe that my set targets and objective are attained and identified by the firm through training program in the company. Employee empowerment effects on employee performance of telecommunication companies. Respondents agreed that I have total freedom to decide how to accomplish my work. The results and findings indicated that Human Resource Management should come up with an effective performance measurement system that rewards hard workers and penalizes ineffective workers. The researcher recommends that all employees should be motivated to ensure they are retained and this will improve performance. In this way overall organizational productivity and effectiveness can be enhanced.